2015
DOI: 10.7567/apex.8.061501
|View full text |Cite
|
Sign up to set email alerts
|

Highly enhanced piezoelectric property of co-doped AlN

Abstract: We propose a series of new compositions of AlN-based piezoelectric material based on the results of first-principles calculation. The composition is expressed by ð y ; 1Ày Þ x Al 1%x N, where the elements α and β are selected to maintain the charge neutrality of the host AlN. We found that the selection of Mg 2+ for α and Hf 4+ and Zr 4+ for β with y = 0.5 show good chemical stability with much better piezoelectric properties than pure AlN. Our results indicate broad compositional freedom for improving the pie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 24 publications
10
39
0
Order By: Relevance
“…In TM Compared to previously reported piezoelectric coefficients e 33 , C 33 , and d 33,f by Yokoyama et al [11,13] and Iwazaki et al [12] there is a qualitative agreement that the quarternaries will be an improvement compared to pure AlN and a competitive alternative to ScAlN. There are, however, some quantitative differences, which is expected because of the different alloy models used.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…In TM Compared to previously reported piezoelectric coefficients e 33 , C 33 , and d 33,f by Yokoyama et al [11,13] and Iwazaki et al [12] there is a qualitative agreement that the quarternaries will be an improvement compared to pure AlN and a competitive alternative to ScAlN. There are, however, some quantitative differences, which is expected because of the different alloy models used.…”
Section: Resultsmentioning
confidence: 58%
“…Here, we investigate the piezoelectric and elastic properties of the nine different quarternary TM x/2 M x/2 Al 1−x N (TM = Ti, Zr, Hf; M = Mg, Ca, Zn) alloys. Of these quarternaries, TiMgAlN [11,12], ZrMgAlN [11][12][13][14], and HfMgAlN [11,12] have only recently begun to be studied theoretically, and only ZrMgAlN [11,13] and HfMgAlN [11] experimentally. Moreover, we investigate the thermodynamic stability of the alloys to determine the possibilities for equilibrium or the need for nonequilibrium synthesis routes.…”
Section: Introductionmentioning
confidence: 99%
“…This is expected to maintain a high electromechanical coupling coefficient, which is attractive for BAW filters 32 . Instead of relying on the +3 oxidation state Sc or Y isovalent with Al, it has been predicted that codoping AlN with Mg of oxidation state +2 and Hf or Zr of oxidation state +4 in 1:1 ratio can lead to a giant enhancement in the piezoelectricity of AlN 33 . Rather remarkably, it has been experimentally found that co doping AlN with Mg and Nb leads to a 400% giant piezoelectricity enhancement 34 .…”
Section: Nitride Extreme-piezoelectrics and Ferroelectricsmentioning
confidence: 99%
“…It remains a challenge to explore better piezoelectric wurtzite materials; there are many reports aiming to enhance piezoelectricity by element doping or codoping into parent materials. [4][5][6][7] Among the wurtzite materials, the highest piezoelectricity has been experimentally discovered for Sc x Al 1−x N (about 25 pC=N for x ∼ 0.5).…”
mentioning
confidence: 99%